2021
DOI: 10.1002/rmb2.12418
|View full text |Cite
|
Sign up to set email alerts
|

A novel trophectoderm biopsy technique for all blastocyst stages

Abstract: Purpose This study was conducted to assess the effectiveness of a new trophectoderm (TE) biopsy method that does not require prior opening of the zona pellucida at the blastocyst stage. Methods TE biopsy was conducted using a modified extrusion method for embryos during the cleavage stage. In this method, culture medium was injected into the perivitelline space to help extrude TE cells from the zona pellucida before TE biopsy. Results Our ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A biopsy is generally performed by aspirating the required amount of TE cells and cutting them by laser irradiation (pulling method) or rubbing them into a holding pipette ( icking method). In this study, we used the pulling method [9] as previous studies indicated that the icking method collects more TE cells than those obtained by the pulling method [7]. The pulling method irradiates the targeted area with a laser, making cell collection easy to control and, thus, ensuring a more accurate collection of the intended number of cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A biopsy is generally performed by aspirating the required amount of TE cells and cutting them by laser irradiation (pulling method) or rubbing them into a holding pipette ( icking method). In this study, we used the pulling method [9] as previous studies indicated that the icking method collects more TE cells than those obtained by the pulling method [7]. The pulling method irradiates the targeted area with a laser, making cell collection easy to control and, thus, ensuring a more accurate collection of the intended number of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies were performed using the pulling method with laser irradiation [9]. Regarding embryo biopsies, tubing, and NGS analyses of cell samples obtained from trophectoderm (TE) biopsies, these were performed as described by Mizobe et al [9] and Takeuchi et al [10].…”
Section: Embryo Biopsy and Ngs Analysismentioning
confidence: 99%
See 1 more Smart Citation